Who are the Diasporas in Malaysia? The Discourse of Ethnicity and Malay(sian) Identity - Khattab, Umi Manickam (SOSIOHUMANIKA, 2010)
ABSTRACT: This paper attempts to offer a new understanding of the âconstructedâ nature of ethnic identity and ethnic-relations in Southeast Asia. Using Malaysia as a case, I first sketch the history of Indian and Indonesian diasporic cultural flows into and influences on the peninsula Malay identity from pre to post-European colonisation. Second, I point out how state-led mediatised essentialising of the Â peninsula âMalayâ as territorial and indigenous (bumiputra) appears to have led to the inclusion and exclusion of the pre and post-colonial Indonesian migrant at various moments in the process of negotiating Malay identity, making of an urban Malay-Muslim and the re-making of a capitalist Muslim-Malay. Third, I argue and maintain that the process of âotheringâ in multicultural Malaysia seems triggered by âontological insecurityâ and âde-traditionalisationâ â as pointed out by Anthony Giddens (1990) â and the hegemonic construction of Malay(sian) identity. Finally, the national culture and identity has been described as a form of imaginative identification as an idea that is simultaneously one of inclusion (e.g. âBangsa Malaysiaâ or Malay plus Indonesian) that provides a boundary around âusâ and one of exclusion (e.g. âbumiputra/bukan bumiputraâ or Malay minus Indonesian) that distinguishes âusâ from âthemâ, where race (the Malay) is symbolically expressed as national and territorial, constructed differently and distinctively.Key Words: Diaspora, media, culture, identity, ethnicity, Islam, Indian, Indonesia, and Malay(sia).About the Author: Assoc. Prof. Dr. Umi Manickam Khattab is Senior Lecturer at the Communications Programme, School of Social Sciences UMS (Malaysia University of Sabah), Locked Bag 2073, 88999 Kota Kinabalu, Sabah, Malaysia. She can be reached at: umi@ums.edu.my and ukhattab@gmail.comHow to cite this article? Khattab, Umi Manickam. (2010). âWho are the Diasporas in Malaysia? The Discourse of Ethnicity and Malay(sian) Identityâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.3, No.2 [November], pp.157-174. Bandung, Indonesia: Minda Masagi Press, UNIPA Surabaya, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (September 10, 2010); Revised (October 15, 2010); and Published (November 20, 2010). Â  Â